A discursividade de enfermeiros da atenção básica relacionada ao tratamento diretamente observado da tuberculose - Andrade, Séfora Luana Evangelista de (2014)
The tuberculosis remais as a worldwide public health problem, being the main second cause of death by infectious disease, after de virus of human immunodeficiency. For the tuberculosis control was proposed a strategy Directly Observed Treatment Short Course, being a directly observed treatment the key element of this strategy. It is known that the nurse is the main actor involved with the completion of this treatment modality, as well as, with the others control actions of tuberculosis. In this sense, this study, having as theoretical and analytical reference the Discourse Analysis, it aims to analyze the discursiveness of basic attention nurses related to the treatment directly observed of tuberculosis. Study of qualitative nature, which counted with the collaboration of 13 (thirteen) female nurses. To obtain the information it was utilized the technique of semidirected interview. Information collection was conducted from August to October 2012. The analysis of discursiveness of nurses on the directly observed treatment reveals that these professionals stand out in the execution of tuberculosis treatment and the senses interpreted in their discourses suggest weakness in the operacionalization of this treatment modality mainly related to lack of involvement of other professionals in the staff. They point out the devaluation and insecurity in performing the directly observed treatment by some professionals, which can reflect in an offer of care not guided in integrality, besides indicating the centralization of actions and overload of work for nurses. In relation to the effects of the senses produced about the difficulties in adhesion to the directly observed treatment, it was observed that the motivation for non-adherence to therapeutic are related to the patients, to the health professionals and to the treatment. Between the difficulties conveys to emphasize that prejudice and stigma contribute to non-adherence to therapeutic, being these problems related to patients and health professionals. The study revealed that fragilities in the operacionalization of the directly observed treatment, as well as the difficulties about therapeutic adhesion, can justify the low percentage of completion of this treatment modality in the city studied. Therefore, it is important to prioritize innovative qualification in order to promote the discourse of the health professional less affected and more accustomed to the care they set the patient free from the disease and stigma that surrounds them, as well as the strengthening of teamwork in basic attention, in the perspective of offering a care more integral and affective to tuberculosis patients in the directly observed treatment.